2017
DOI: 10.1093/fampra/cmx107
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to implement screening for alcohol consumption in Spanish hypertensive patients

Abstract: GPs did not consider alcohol consumption a relevant factor for HT and, additionally, found it difficult to deal with alcohol problems. Some of the barriers for alcohol screening could be overcome through structural changes in the health system, such as empowering GPs to treat alcohol use disorders (rather than a single focus on implementing preventive strategies) by enhancing training in alcohol diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
11
1
Order By: Relevance
“…Overall, professionals considered handing out brochures as an unwelcome extra workload. According to recent studies, general practitioners in Spain see around 37 patients per day 18 (higher than in our sample: 21.9 per day) and each appointment takes between 2 and 13 min 28,29 being less than the recommended 15 min by the College of Medicine 30 and far from the 22.5 min in Sweden. 28 In the ODHIN project, patient referral to eBI took 5.5 min, 11 representing a 42 percent time increase per appointment for Spanish practitioners.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Overall, professionals considered handing out brochures as an unwelcome extra workload. According to recent studies, general practitioners in Spain see around 37 patients per day 18 (higher than in our sample: 21.9 per day) and each appointment takes between 2 and 13 min 28,29 being less than the recommended 15 min by the College of Medicine 30 and far from the 22.5 min in Sweden. 28 In the ODHIN project, patient referral to eBI took 5.5 min, 11 representing a 42 percent time increase per appointment for Spanish practitioners.…”
Section: Discussioncontrasting
confidence: 57%
“…4,16,17 One example is the recent research of our group in order to explore the UP of BI in patients with both high blood pressure and risky alcohol use. 18 Nevertheless, lack of UP for e-health is not only limited to the health care provider of BI but also to the patients, being for instance the acceptance of the “Chronic disease self-monitoring System” mediated by UP. 19 Consequently, UP of professionals is one of the most frequent individual factors, which affect the implementation of e-health.…”
Section: Discussionmentioning
confidence: 99%
“… McAvoy (2001) [ 16 ] Australia, Canada, Denmark, France, Hungary, Italy, New Zealand, Norway, Poland, Russia UK Semi-structured interview, 126 physicians Intervention characteristics Evidence strength and quality: proven efficacy of early intervention Outer setting Patient needs and resources: patients’ requests for advice about alcohol consumption External policy and incentives: more societal concern about alcohol; government policy favoured preventive medicine; professional recognition of early intervention by medical bodies; policy making preventive medicine a higher status in the medical profession Inner setting Organizational incentives and rewards: financial reimbursement for training in early intervention; health scheme reimbursements; training in early intervention for hazardous alcohol consumption was recognized for continuing medical education credits; providing early intervention for hazardous alcohol consumption was recognized for quality assurance credits Available resources: quick and easy counselling techniques were available; quick and easy diagnostic questionnaires were available Characteristics of individuals Knowledge and beliefs: gained knowledge on alcohol in medical school Intervention characteristics Cost: lack of time Outer setting Patient needs and resources: private health insurance did not reimburse patients for alcohol counselling; patient’s unwillingness to be asked; patient’s unwillingness for alcohol counselling Cosmopolitanism: lack of referral services External policy and incentives: lack of government policy support Inner setting Organizational incentives and rewards: lack of financial reimbursement or incentives in the contract Available resources: lack of training and education for early intervention in medical schools Characteristics of individuals Knowledge and beliefs: lack of counselling skills for reducing alcohol consumption Miller (2006) [ 74 ] USA Focus group, 18 different health professionals (e.g. medical assistants, nurses) Intervention characteristics Adaptability: computer-based method for screening Inner setting Structural characteristics: teamwork Relative priority: prioritization Intervention characteristics Cost: lack of time Characteristics of individuals Knowledge and beliefs: lack of knowledge of screening tools; fear of harming patient-physician relationship Miquel (2018) [ 75 ] Spain Survey, 867 physicians Characteristics of individuals Knowledge and beliefs: higher levels of graduate education and postgraduate education in alcohol were more likely to provide screening Intervention characteristics Cost: lack of time <...>…”
Section: Resultsmentioning
confidence: 99%
“…Possession of knowledge and positive beliefs about the intervention were reported as facilitators by 35 studies [ 13 , 14 , 16 – 19 , 24 , 35 , 39 , 40 , 45 , 46 , 49 , 51 – 53 , 55 – 57 , 59 – 61 , 64 , 70 , 72 , 73 , 75 , 78 , 80 , 81 , 83 , 85 , 86 , 89 , 27 ]. For example, familiarity with expert guidelines, perceived knowledge and skills of early alcohol intervention, and receiving higher levels of education training in alcohol were significantly associated with screening or intervention activity in one multi-country study and four others in Sweden, the USA, Spain, and Norway [ 18 , 40 , 55 , 61 , 75 ]. On the other hand, lack of knowledge, skills, or low awareness of alcohol problems were cited as barriers by 25 studies [ 13 , 15 , 16 , 20 22 , 24 , 26 , 35 , 37 , 41 , 57 – 60 , 64 , 68 , 70 , 74 , 78 80 , 82 , 91 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…23 Asking questions about alcohol consumption is associated with a feeling of stigmatising the patient according to 16.5% of Spanish GPs. 27 In France, alcohol remains a taboo subject. 28 In the present study, the participants indicated that they felt fear or denial on the part of their GP.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%